The Analysis of Inflation, Exchange rate, and Benchmark Interest Rate (BI rate) Influences on the Indonesia Composite Index (ICI) - Tubagus Hanuransyah; Daryono Soebagiyo (Junal Ilmu Manajemen, 2023)
This study analyzes the correlation and influence rates of inflation, Bank Indonesia, and the Dollar Exchange (USD/IDR) on the Indonesia Composite Index(ICI) in Indonesia from 2001 to 2021. The type of study used explanatory research with quantitative approach. The research data is in the form of secondary data based on the period in the form of ICI, benchmark interest rate, inflation, and rupiah exchange rate on the US dollar (KURS) obtained from Bank Indonesia (BI), the Indonesia Stock Exchange (IDX), and the Central Statistics Agency (BPS). This study's data complements the latest month's data from the inflation rate, BI Rate, USD/IDR Exchange rate, and combination of the Stock Price Index(ICI) for 2001 to 2021. The analysis method in this study used multiple linear regression models and Ordinary Least Squares (OLS). The results showed that the Ordinary Least Square (OLS) relies on the overall movement of exchange rates in the interest rate based on the Composite IDX.